Factors associated with first-line antiretroviral treatment failure in adult HIV-positive patients: a case-control study from Ethiopia - Yihienew Mequanint Bezabih; Fekadu Beyene; Woldesellassie M. Bezabhe (BMC Infectious Diseases, 2019)
Abstract Background Treatment failure has become a significant challenge in patients taking antiretroviral therapy (ART). The aim of the present study was to identify risk factors for first-line ART failure among patients attending clinical follow-up. Methods A 1:2 matched case-control study (by age, sex, and treatment duration since initiated on ART) was conducted from June 2015 to July 2017 on adult patients (aged ≥15 years) who were on ART for at least 6 months. Cases were selected from patients who were switched to second-line ART after first-line ART failure (viral load ≥1000 copies/mL). Controls were randomly selected from patients on first-line ART with viral load < 50 copies/mL. Data were collected using an interview questionnaire, reviewing chart and electronic health records and laboratory tests. Multivariate logistic regression analysis was performed to identify risk factors for treatment failure. Results Of the 273 patients who participated in this study, 55% were males. Ninety-one cases were compared with 182 controls. The median age of participants was 40 years and the median duration of treatment since initiated on ART was 69 months. Independent risk factors associated with first-line antiretroviral treatment failure were discontinuation of ART (adjusted odds ratio (AOR) = 9.8, 95% confidence interval (CI): 4.0–23.8), baseline CD4 lymphocyte count ≤50 cells/mm3 (AOR = 3.8, 95% CI: 1.5–9.6) and persistent diarrhea (AOR = 4.4, 95% CI: 1.5–13.2). The risk of ART failure was high and comparable whether the duration of ART discontinuation was greater or less than 1 month (crude odds ratio (COR) = 6.3 and 8. 5 respectively, p-value < 0.001). Frequent eating of a diet containing wheat or barley (AOR = 2.3, 95% CI: 0.9–5.4) showed a trend to be a risk factor for first-line ART failure (p-value = 0.064). Conclusions Our findings underscore the importance of avoiding ART discontinuation of any duration, early initiation of ART and diarrhea management to prevent first-line ART failure.